2015
DOI: 10.1039/c5ra07983g
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional polybenzoxazine nanocomposites containing photoresponsive azobenzene units, catalytic carboxylic acid groups, and pyrene units capable of dispersing carbon nanotubes

Abstract: A new multifunctional benzoxazine monomer Azo-COOH-Py BZ includes an azobenzene unit, a carboxylic acid group, and a pyrene moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 45 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…TGA analysis revealed that, without UV irradiation, the poly(dicoumarin Py BZ)/SWCNT (3 wt%) nanocomposite had a higher decomposition temperature and char yield than those of the coumarin‐containing PBZ, presumably because of the effect of the increased crosslinking density and nano‐reinforcement. We also prepared a trifunctional Azo‐COOH‐PyBz monomer through condensation of Azo‐COOH, 1‐aminopyrene (pyrene‐NH 2 ), and paraformaldehyde . Because Azo‐COOH‐PyBz contained a pyrene unit, it improved the dispersion of CNTs through π‐stacking; because of the presence of the carboxyl group and the catalytic effect of the SWCNTs, the maximum exothermic curing peak for the Azo‐COOH‐PyBz/SWCNT hybrid complexes shifted to lower temperature, compared with that of poly(Azo‐COOH‐PyBz), based on DSC thermograms.…”
Section: Pbz/carbon Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…TGA analysis revealed that, without UV irradiation, the poly(dicoumarin Py BZ)/SWCNT (3 wt%) nanocomposite had a higher decomposition temperature and char yield than those of the coumarin‐containing PBZ, presumably because of the effect of the increased crosslinking density and nano‐reinforcement. We also prepared a trifunctional Azo‐COOH‐PyBz monomer through condensation of Azo‐COOH, 1‐aminopyrene (pyrene‐NH 2 ), and paraformaldehyde . Because Azo‐COOH‐PyBz contained a pyrene unit, it improved the dispersion of CNTs through π‐stacking; because of the presence of the carboxyl group and the catalytic effect of the SWCNTs, the maximum exothermic curing peak for the Azo‐COOH‐PyBz/SWCNT hybrid complexes shifted to lower temperature, compared with that of poly(Azo‐COOH‐PyBz), based on DSC thermograms.…”
Section: Pbz/carbon Nanocompositesmentioning
confidence: 99%
“…We also prepared a trifunctional Azo-COOH-PyBz monomer through condensation of Azo-COOH, 1-aminopyrene (pyrene-NH 2 ), and paraformaldehyde. [94] Because Azo-COOH-PyBz contained a pyrene unit, it improved the dispersion of CNTs through π-stacking; because of the presence of the carboxyl group and the catalytic effect of the SWCNTs, the maximum exothermic curing peak for the Azo-COOH-PyBz/SWCNT hybrid complexes shifted to lower temperature, compared with that of poly(Azo-COOH-PyBz), based on DSC thermograms. TGA analysis was used to investigate the effect of SWCNTs and MWCNTs on the thermal stability of Azo-COOH-PyBz after thermal curing polymerization; it revealed that the char yield and value of T d of poly(Azo-COOH-PyBz) increased to greater degrees in the presence of SWCNTs than in the presence of MWCNTs, possibly because of the greater thermal conductivity of the SWCNTs within the PBZ matrix.…”
Section: Pbz/cnt Nanocompositesmentioning
confidence: 99%
“…The high curing temperature of benzoxazines is one of the problems that limits their widespread application [ 23 ]. The main way to solve this problem is to use catalysts [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] such as phenols [ 24 , 25 ], strong acids [ 26 ], carboxylic acids [ 27 , 28 ] and Lewis acids [ 29 , 30 , 31 , 32 , 33 ]. All listed compounds are effective catalysts for the homopolymerization of benzoxazines; however, due to their high catalytic efficiency, one cannot use them in a mixture with the most common reactive compounds, such as epoxy resins, since they cause earlier curing of epoxy oligomers, thereby complicating the polymerization of benzoxazine.…”
Section: Introductionmentioning
confidence: 99%
“…The physical characteristic of PBZs can be improved using three main approaches. First, through the addition of inorganic materials (e.g., clay [ 6 ], polyhedral oligomeric silsesquioxane (POSS) [ 7 , 8 ], carbon nanotubes [ 9 , 10 , 11 , 12 ], graphene [ 13 ]) to form PBZ nanocomposites. Second, through use of functionalized BZ monomers presenting, for example, allyl, vinyl, pyrene, nitrile, methacryloyl, benzoxazole, and carboxylic acid groups [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, through blending with other thermal plastics or thermoset resins (e.g., poly( N -vinyl-2-pyrrolidone) (PVP), polyurethane, epoxy resin) [ 21 , 22 , 23 ]. As an example of the second approach, the Azo-COOH BZ monomer contains both azobenzene and COOH units, with the latter serving as a catalyst that lowers the curing temperature relative to that of traditional BZ monomers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%